The Impact of Ergonomically Designed Workstations on Shoulder EMG Activity during Carpet Weaving - Majid Motamedzade; Davood Afshari; Alireza Soltanian (Tabriz University of Medical Sciences, 2014)
Background: The present study aimed to evaluate the biomechanical exposure to the trapezius muscle activity in female weavers for a prolonged period in the workstation A (suggested by previous studies) and workstation B (proposed by the present study). Methods: Electromyography data were collected from nine females during four hours for each ergonomically designed workstation at the Ergonomics Laboratory, Hamadan, Iran. The design criteria for ergonomically designed workstations were: 1) weaving height (20 and 3 cm above elbow height for workstations A and B, respectively), and 2) seat type (10° and 0° forwardsloping seat for workstations A and B, respectively). Results: The amplitude probability distribution function (APDF) analysis showed that the left and right upper trapezius muscle activity was almost similar at each workstation. Trapezius muscle activity in the workstation A was significantly greater than workstations B (P<0.001). Conclusion: In general, use of workstation B leads to significantly reduced muscle activity levels in the upper trapezius as compared to workstation A in weavers. Despite the positive impact of workstation B in reducing trapezius muscle activity, it seems that constrained postures of the upper arm during weaving may be associated with musculoskeletal symptoms.